Emergency Use of a Custom Distal Femoral Replacement System for Acute Periprosthetic Fracture with Catastrophic Implant Failure: A Case Report. Issue 3 (12th July 2021) - Emara, Ahmed K.; Ng, Mitchell; Krebs, Viktor E.; Piuzzi, Nicolas S.
Abstract : Case: A 54-year-old man with arthrogryposis and 7 failed revision knee arthroplasties presented with acute periprosthetic fracture and catastrophic failure of a modular-hinged implant at the stem-condylar junction. To prevent total femoral replacement, above-knee amputation, or fusion, a custom distal femoral replacement was offered. The implant was procured during the emergency hospitalization and cemented with the proximal stem engaging the distal ipsilateral total hip arthroplasty, creating endofemoral implant continuity. The patient returned to nonassisted ambulation with stable implant fixation at the 1-year follow-up. Conclusion: Custom distal femoral replacing implants are feasible for complex emergency knee-salvage revisions with poor bone stock to avert more radical reconstruction alternatives.